"Insurrección": Power Relations in Spanish Newspapers on the Referendum of Independence of Catalunya - Aquino, Evelyn (2023)
We propose the study of the ways of construction of discourses about the Catalunya Independence Referendum in the newspapers El País, El Periódico de Catalunya, El Mundo and La Vanguardia. We analyzed the covers of the periodicals on October 2, 2017. The research method used is Critical Discourse Analysis (CDA) through the multidisciplinary approach of van Dijk's (2005). We contextualized the historical trajectory of Catalunya's autonomist struggle and the institutional nature of newspapers. We observed that the newspapers are rivals in their ideological positions, with regard to the discourses used, we found that El País and El Mundo delegitimized the consultation, mischaracterizing the historical aspirations of the separation proposal while El Periódico de Catalunya and La Vanguardia exalted the positive result and ratified their militant profile in the independence cause.